2013
DOI: 10.2118/146322-pa
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Wettability Alteration and Oil-Recovery Improvement by Low-Salinity Water in Sandstone Rock

Abstract: Optimization of any oil-recovery process is based on understanding of the recovery mechanisms, whereas the underlying mechanisms of improving oil recovery by low-salinity-water injection are still debated. Wettability alteration is one of the mechanisms suggested to be the primary mechanism of low-salinity water. Therefore, wettability alteration by low-salinity water in sandstone reservoirs is examined by using the contact-angle technique. The effect of changing ionic strength on the electrokinetic charges is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(89 citation statements)
references
References 19 publications
3
86
0
Order By: Relevance
“…For all dispersions, the zeta potential becomes more negative (there is more double-layer expansion) at lower salinities. Nasralla et al have observed similar results for a more diverse variety of systems [32]. In addition to the same three brines studied by Alotaibi et al, Nasralla et al have also examined aquifer water diluted by a factor of ten and deionized water.…”
Section: Zeta Potential Contact Angle Oil Recovery and Afm Measurementioning
confidence: 72%
See 2 more Smart Citations
“…For all dispersions, the zeta potential becomes more negative (there is more double-layer expansion) at lower salinities. Nasralla et al have observed similar results for a more diverse variety of systems [32]. In addition to the same three brines studied by Alotaibi et al, Nasralla et al have also examined aquifer water diluted by a factor of ten and deionized water.…”
Section: Zeta Potential Contact Angle Oil Recovery and Afm Measurementioning
confidence: 72%
“…At 1 mM, the zeta potential for all three brine/silica dispersions is − 33 mV so that the change with salinity is more pronounced for the larger cations. At the same concentration, the brine/rock and brine/oil zeta potentials tend to be more negative if the brine contains monovalent cations as opposed to divalent cations [29,32,27]. This may be because divalents have a stronger influence on the ionic strength and electrostatic screening as evident in Eq.…”
Section: Zeta Potential Contact Angle Oil Recovery and Afm Measurementioning
confidence: 99%
See 1 more Smart Citation
“…recovery modes (Webb et al 2005;Zhang et al 2007;Lager et al 2007;Agbalaka et al 2009) while others showed no improvement in tertiary mode (Rivet et al 2010;Nasralla et al 2011). Extensive studies have been conducted to determine the LSW recovery mechanisms, and debatable conclusions were proposed.…”
mentioning
confidence: 99%
“…Furthermore, there is direct evidence that wettability altered to more water-wet during low salinity water flooding [9], [10]. Accordingly, initial and final wettability's are key indices which have been evaluated.…”
Section: Wettability Effects and Its Alterationmentioning
confidence: 99%